Purity determination on silkworm hybrid rate using RAPD technique - ZHONG Bo-xiong; ZHANG Jin-wei; DING Nong; TAO jing-ya; LU Yun-chong (浙江大学学报. 农业与生命科学版)
It was found that specifity of DNA fingerprinting of the genome from individual silkworm can be characterized on three different levels, namly, species-specific, variety-specific and individual-specific level. Only pecularity of DNA that are varietie-specific can serve as juge criterion for purity determination on the hybrid. The same PCR result can be amplified by DNA template from a single silkworm egg or a newly hatched larva and from silkworm gland cells. So fingerprint based on DNA at the egg stage is promising to be used in rapidly assessing purity of hybrid.